ANALYSIS SERVICE LEVEL AHMAD YANI ROAD SEGMENT KM. 7 DISTRICT OF BANJAR - Dyah Ayu Vertikasari; Rosehan Anwar (CERUCUK, 2017)
Banjar Regency is one of the areas with a solid growth growth rate. This resulted in the increasing number of vehicles can lead to movement of large traffic flows. Therefore, research needs to be done on the level of service on the road Ahmad Yani Km. 7 in order to determine the need for handling or not.The method used is the analysis of three models Greenshields, Greenberg, Underwood, and method Manual Capacity Road Indonesia (MKJI) 1997 provides guidance to get the level of service road from a road.The model equation for Banjarbaru-Banjarmasin flow direction is Greenberg model, y = -18.25 ln (x) + 113,63, R value 0,914 with maximum volume 3396,383 smp / hour, while for Banjarmasin- Banjarbaru with Greenberg model is y = -19.31 ln (x) + 119,66, R value 0,854, and obtained when maximum volume equal to 3489,146 smp / hour. With MKJI 1997 method, the capacity of 4280,76 pcu / hour for both traffic flow.Based on the predictions made, the results obtained that in the first year, the level of service on the road Ahmad Yani Km. 7 Banjarmasin has entered the F category and needs to be handled. The solution that can be given is by maximizing the use of public transportation and in the form of transfer of the road by using alternative path. Keywords: Greenshields, Greenberg, Underwood, MKJI, Prediction.